Translingual pedagogical perspectives : engaging domestic and international students in the composition classroom - Kiernan, Julia, 1980-; Frost, Alanna, 1969-; Blum-Malley, Suzanne, 1966- (Utah State University Press, 2021)
"Addresses the movement toward translingualism in writing classrooms and demonstrates pedagogical strategies faculty can take to represent domestic and international students' perspectives. Contributors explore approaches used by diverse programs, insisting traditional strategies need to be reimagined if they are to engage the growing number of diverse learners"--